Evaluating the implementation of an electronic-based government system: A lesson from Sukabumi District - Siella Islami Bahagia; M. Rijal Amirulloh; Andi Mulyadi (Universitas Merdeka Malang, 2025)
In the era of globalisation, the Indonesian government has promoted digital transformation through the Electronic-Based Government System (SPBE), as outlined in Presidential Regulation No. 95 of 2018. This study aims to evaluate the implementation of SPBE in Sukabumi Regency using a qualitative case study method. The evaluation is conducted using the maturity level model based on the Ministry of PAN-RB Regulation No. 59 of 2020, which includes four key domains: internal SPBE policies, SPBE governance, SPBE management, and SPBE services. The results of this study show a notable improvement in the SPBE index of Sukabumi Regency, which increased from 1.56 in 2021 to 3.08 in 2023. This indicates substantial progress in the local government's efforts to implement digital governance. The evaluation highlights various strengths and weaknesses in each of the four domains, showing which aspects have improved and which still require development. Furthermore, this study incorporates feedback from multiple stakeholders, including local government officials, SPBE managers, and service users, to gain a more comprehensive understanding of the implementation process. These insights are used to formulate recommendations aimed at enhancing the effectiveness, efficiency, and quality of public services through SPBE. The findings are expected to support Sukabumi Regency in achieving a higher SPBE index rating and contribute to broader national e-government goals.